Changes in circulating endothelial progenitor cells predict responses of multiple myeloma patients to treatment with bortezomib and dexamethasone - Wang,L. (2015)
Four cycles of chemotherapy are required to assess responses of multiple myeloma (MM) patients. We investigated whether circulating endothelial progenitor cells (cEPCs) could be a biomarker for predicting patient response in the first cycle of chemotherapy with bortezomib and dexamethasone, so patients might avoid ineffective and costly treatments and reduce exposure to unwanted side effects. We measured cEPCs and stromal cell-derived factor-1α (SDF-1α) in 46 MM patients in the first cycle of treatment with bortezomib and dexamethasone, and investigated clinical relevance based on patient response after four 21-day cycles. The mononuclear cell fraction was analyzed for cEPC by FACS analysis, and SDF-1α was analyzed by ELISA. The study population was divided into 3 groups according to the response to chemotherapy: good responders (n=16), common responders (n=12), and non-responders (n=18). There were no significant differences among these groups at baseline day 1 (P>0.05). cEPC levels decreased slightly at day 21 (8.2±3.3 cEPCs/μL) vs day 1 (8.4±2.9 cEPCs/μL) in good responders (P>0.05). In contrast, cEPC levels increased significantly in the other two groups (P<0.05). SDF-1α changes were closely related to changes in cEPCs. These findings indicate that change in cEPCs at day 21 in the first cycle might be considered a noninvasive biomarker for predicting a later response, and extent of change could help decide whether to continue this costly chemotherapy. cEPCs and the SDF-1α/CXCR4 axis are potential therapeutic targets for improved response and outcomes in MM patients.